Pengaruh Work-Life Balance Dan Target Kerja Terhadap Kesehatan Mental Pegawai Melalui Motivasi Sebagai Variabel Intervening Pada Dinas Sosial (P3appkb) Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk Dan Keluarga Berencana Kabupaten Dharmasraya - Rahmawati .; Dori Mittra Candana; Mardhatila Fitri Sopali (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the mental health of public sector employees who face high work demands, particularly those working at the Social Affairs Office P3APPKB of Dharmasraya Regency. Imbalances in work–life balance and work target pressures are assumed to influence employee motivation and mental health. The population of this study consisted of all employees of the Social Affairs Office P3APPKB, totaling 52 respondents. The main objective of this research is to examine the effect of work–life balance and work targets on employees’ mental health, with motivation acting as an intervening variable.